EFISIENSI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI PADA INDUSTRI KERAJINAN TULANG DI DESA TAMPAKSIRING KABUPATEN GIANYAR - Sugiyani, Komang Mitha; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The growth of the industrial sector is strongly influenced by the scale of production if the larger scale of its production business will show the level of efficiency in the use of factors of production or high inputs. The purpose of this research simultaneously and partially is to determine the effect of capital, work, and raw materials on production and to determine the level of efficiency and economies of scale. The data used in this study are primary data, namely by distributing questionnaires to bone craft business owners in Tampaksiring Village. The sample used in this study was 42 business units in Tampaksiring Village. The sampling technique used is saturated sampling. Using multiple linear regression analysis techniques. The results showed that capital, labor and raw materials simultaneously had a significant effect on production. Capital partially has a significant effect on production, labor has a partially significant effect on production, raw materials have a partially significant effect on production. The level of capital and labor efficiency is efficient while raw materials are inefficient. Economies of scale are in decreasing return to scale. The most influential variable on production is capital. Keywords: Capital, Labor, Raw Materials, Production